2017
DOI: 10.21924/cst.2.2.2017.59
|View full text |Cite
|
Sign up to set email alerts
|

Interference effect during word-task and colour-task in incongruent stroop-task

Abstract: Stroop-task is one of the most popular studies to check the ability of decision-making and cognitive process during high interference activity in the brain. In the incongruent Stroop-task, the difference between the colour that we read and the colour that we see produces high interference activities in the brain. This research aims to analyse the activity differences in each part of the brain during colour-task and word-task. This study investigates how well the ability of decision-making and cognitive process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Our consensus showed that cognitive exertion is greater when the activity is combined with different cognitive stressors, whereas an isolated stressor might not be sufficient to elicit MF. Regarding the MF protocol used to induce MF, such as incongruent Stroop-colour task, the protocol should require ongoing conscious decision-making together with selective attention to challenge the ability to inhibit cognitive interference (Brown et al, 2020;Hotama et al, 2017;Van Cutsem et al, 2017). Therefore, it appears that a prerequisite to induce MF in orienteering is whether the task sufficiently challenges the orienteers' cognition.…”
Section: The Causes Of Mental Fatiguementioning
confidence: 99%
“…Our consensus showed that cognitive exertion is greater when the activity is combined with different cognitive stressors, whereas an isolated stressor might not be sufficient to elicit MF. Regarding the MF protocol used to induce MF, such as incongruent Stroop-colour task, the protocol should require ongoing conscious decision-making together with selective attention to challenge the ability to inhibit cognitive interference (Brown et al, 2020;Hotama et al, 2017;Van Cutsem et al, 2017). Therefore, it appears that a prerequisite to induce MF in orienteering is whether the task sufficiently challenges the orienteers' cognition.…”
Section: The Causes Of Mental Fatiguementioning
confidence: 99%
“…The brain wave analysis covered the nineteen electrode sites: Fp1, Fp2, F7, F3, Fz, F4, F8, T3, C3, Cz, C4, T4, T5, P3, Pz, P4, T6, O1, and O2. We established epochs for analyzing data segments [28,29]. A Fourier transform was performed for each 30-second epoch to obtain the frequency domain's brain wave parameters, which were already also used in the previous study [21].…”
Section: Signal Processing and Feature Extractionmentioning
confidence: 99%
“…One type of task used in measuring cognitive performance is the Stroop Color-Word Task (SCWT), commonly referred to as the Stroop Test, where subjects are asked to read a series of colored words and expressions as quickly as possible [42][43][44]. The representation of the Stroop Color Test type of cognitive task for working in industry lies in the ability of workers to cope with distractions, process information quickly and accurately, and handle complex and diverse tasks [45].…”
Section: Introductionmentioning
confidence: 99%